The Effect of Work-Life Balance And Workload on Employee Job Satisfaction in the Creative Media Industry at MSME Scale In Samarinda - Syahbana, Muhammad Andrew; Anwar, Khairil (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Work-life balance and workload are two aspects of improving employee well-being and job satisfaction that are increasingly receiving attention. Given the importance of this topic in the MSME sector, this study fills the gap in the limited literature on the influence of these two factors in the creative media industry. The contribution of this study is to provide new insights for companies in managing these factors to improve employee performance and well-being. This study used a quantitative approach with multiple linear regression techniques to examine the impact of work-life balance and workload on job satisfaction. Data were collected through questionnaires distributed to 150 people working in a creative media company on an MSME scale in Samarinda. According to the study's findings, work-life balance has the biggest impact on these two factors, significantly affecting employee job satisfaction. It is demonstrated that both independent variables can account for 75.4% of the variation in work satisfaction, with a coefficient of determination (R2) of 0.754, while 24.6 percent is influenced by external variables not included in this research model. Workload has a favorable and considerable impact on job satisfaction, although work-life balance has a small but positive effect. The study's findings suggest that increased work-life balance and effective task management can boost worker job satisfaction. Therefore, to achieve organizational goals, businesses are encouraged to maintain and improve work-life balance and manage workload properly to improve employee well-being and satisfaction.